Reading the distance : decoding the autobio(graphic) novel, Portrait in pieces - Gauche, Catherine (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Visual Arts. Illustration))--University of Stellenbosch, 2009.